The Impact of the Panduri Berseri Program on the Economic Independence - Mumayyizah Sabila Rosyadi; Ana Kumalasari; Sri Kasiami (Universitas Muhammadiyah Gorontalo, 2026)
The Sustainable Development Goals (SDGs) are global development goals expected to bring change to both developing and developed countries. In the 17 goals, the eighth goal states decent work and economic growth. The government and the private sector are competing to achieve this global goal. In Indonesia, the regulation of the Minister of State-Owned Enterprises No. PER-1 / MBU / 03 / 2023 concerning Special Assignments and Social and Environmental Responsibilities of State-Owned Enterprises and Law No. 40 of 2007 concerning Limited Liability Companies (UU PT) it is stated that companies with companies involving natural resources are required to carry out Social and Environmental Responsibilities or can be known as Corporate Social Responsibility (CSR), one of which can be through an ecotourism program that functions as a form of conservation to protect the environment, by utilizing nature as a tourist destination while also functioning as a learning medium, by prioritizing sustainability. Using the CSR pyramid theory, ISO 26000, ecotourism, and other supporting theories, this study will employ quantitative methods in SPSS and Microsoft Excel to analyze data from questionnaires distributed by researchers. This study will analyze the impact of the Panduri Berseri ecotourism program on the community's economic independence, using perceptions from the surrounding community. Panduri Berseri is an ecotourism-based CSR (Corporate Social Responsibility) program implemented by PT Pertamina Patra Niaga Fuel Tuban. This study focuses on the program's benefits from the perspective of the Tasikharjo Village community. The Panduri Berseri ecotourism program can have a significant impact on the surrounding community. Although the impact is still relatively minimal, the impacts include community involvement in management and empowerment, as well as indirectly providing entrepreneurial stalls for the Tasikharjo village community.